Tennis superstars: The relationship between star status and demand for tickets. Issue 2 (April 2020) - Chmait, Nader; Robertson, Sam; Westerbeek, Hans; Eime, Rochelle; Sellitto, Carmine; Reid, Machar
Highlights: Players considerably influenced demand for attendance at the Australian Tennis Open. Evident individual-player causal effects on ticket sales. Performance ratings are imprecise representatives of the pulling power of players. Star status can be used to inform business decisions and drive commercial outcomes. Abstract: Akin to other sports, professional tennis is urged to adopt a consumer-centred strategy and understand the influence of the star status of elite players on demand for its core product. Measuring the impact that tennis players have on demand for match attendance remains a key element towards achieving that goal. Using data from the Australian Open ticket sales, the authors demonstrate how individual players have influenced stadium attendance at the Grand Slam. Findings indicate that some players are associated with a strong positive impact on demand for tickets, above and beyond their performance ratings, reflecting their value to the Australian Open. The authors discuss how this star status can be used to inform business decisions related to tournament management, match scheduling, and determining player appearance fees, to ultimately drive better commercial outcomes and deliver a world-class sporting event. The findings have implications for tournament organisers, player managers and those that market player activities.